2020
DOI: 10.1111/flan.12494
|View full text |Cite
|
Sign up to set email alerts
|

Culture and vision in virtual reality narratives

Abstract: The Challenge Immersion in virtual reality environments can unite language, place, and community as students experience highly contextualized real-world environments in visual, auditory, and sensory modalities. How can virtual reality enhance foreign language students' ability to envision and understand the diverse and multifaceted nature of target cultures?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…18 articles investigated AR and VR supported speaking, e.g., [26][27][28]. 10 studies examined AR and VR for writing, e.g., [29][30][31], and another 10 discussed AR and VR enhanced cultural learning, e.g., [32][33][34]. In addition, AR and VR tools were used to promote development of language skills and knowledge such as reading, e.g., [35,36], listening, e.g., [37,38], integral language learning, e.g., [39,40], Chinese character, e.g., [41,42]; grammar learning e.g., [43,44] and English alphabet [45,46].…”
Section: The Data Coding and Analysis Processesmentioning
confidence: 99%
“…18 articles investigated AR and VR supported speaking, e.g., [26][27][28]. 10 studies examined AR and VR for writing, e.g., [29][30][31], and another 10 discussed AR and VR enhanced cultural learning, e.g., [32][33][34]. In addition, AR and VR tools were used to promote development of language skills and knowledge such as reading, e.g., [35,36], listening, e.g., [37,38], integral language learning, e.g., [39,40], Chinese character, e.g., [41,42]; grammar learning e.g., [43,44] and English alphabet [45,46].…”
Section: The Data Coding and Analysis Processesmentioning
confidence: 99%
“…Despite the significant benefits that VR offers for language and intercultural education, there have been relatively few studies exploring its use in cultural learning and crosscultural competence among teachers and students (e.g. Mills et al, 2020;Parmaxi, 2023;Xie et al, 2021). Parmaxi (2023) conducted a systematic review of VR in language learning, drawing from 17 high-impact journals and conferences in CALL and educational technology, and found that cultural awareness is one of the least-studied skills in VR use and should be a priority for future research.…”
Section: Virtual Reality In Language Educationmentioning
confidence: 99%
“…VR technology and its different variations [49] have very high potential for implementation in various areas, including social [50], cultural [51][52][53], economic [54], medical [55][56][57][58] and military [59][60][61]. However, one common area that links all of the above is education.…”
Section: Educational Use Of Vrmentioning
confidence: 99%